2010
DOI: 10.5009/gnl.2010.4.3.345
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the Plasticity Region Genes of Helicobacter pylori and Gastroduodenal Diseases in a High-Prevalence Area

Abstract: Background/Aims: Genes associated with the Helicobacter pylori (H. pylori) plasticity region may play a role in the pathogenesis of H. pylori. We compared the genes jhp0940, jhp0947, and jhp0986 in H. pylori isolates from patients with different gastroduodenal diseases and in different age groups. Methods: The H. pylori hyperplasticity region genes jhp0940, jhp0947, and jhp0986 were studied by PCR. We also evaluated whether these genes were related to the cytotoxin-associated gene (cagA) and histology findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…The presence of cagA and jhp0947 in the H. pylori strains was associated with the severity of gastritis in the subset of patients without duodenal ulcer or gastric cancer (16). Moreover, Yakoob et al (30) reported that jhp0947 was significantly associated with chronic active inflammation, and we also showed that the jhp0947 status was associated with a significantly increased risk of corpus mucosal atrophy. The presence of jhp0947 was completely linked with that of jhp0949 and was roughly associated with that of jhp0945 (6).…”
Section: Discussionsupporting
confidence: 63%
“…The presence of cagA and jhp0947 in the H. pylori strains was associated with the severity of gastritis in the subset of patients without duodenal ulcer or gastric cancer (16). Moreover, Yakoob et al (30) reported that jhp0947 was significantly associated with chronic active inflammation, and we also showed that the jhp0947 status was associated with a significantly increased risk of corpus mucosal atrophy. The presence of jhp0947 was completely linked with that of jhp0949 and was roughly associated with that of jhp0945 (6).…”
Section: Discussionsupporting
confidence: 63%
“…DupA) component of the Tfs4 T4SS, and most likely the Tfs4 T4SS itself, are more strongly associated with a risk of duodenal ulcer disease [ 25 ]. However, no equivalent studies to our awareness have overtly reported the disease association of tfs3 virB4 or any other ( vir gene) marker of the Tfs3 T4SS, although several have reported an association of ctkA with increased or decreased risk of gastroduodenal disease in some populations [ 14 , 16 , 18 , 19 ]. Of these, the study of Occhialini et al [ 14 ] indicated an association of ctkA ( jhp0940 ) with strains isolated from gastric cancer patients, where 42% of strains encoded jhp0940 compared with none of the gastritis isolates.…”
Section: Discussionmentioning
confidence: 96%
“…The 5′ region of jhp0947 is a homologue with jhp0477 ( hp0528 ), which forms part of cag PAI (virB9 homologue) and is involved in the structural region of T4SS (type IV secretion system) . The presence of these genes is associated with DU, DU, or GC with variable frequency between adult isolates from different geographic regions . One study showed that the disruption of these three genes significantly reduced the capability of inducing the production of IL‐12 in THP‐1 monocytic cells .…”
Section: Discussionmentioning
confidence: 99%
“…The 5 0 region of jhp0947 is a homologue with jhp0477 (hp0528), which forms part of cagPAI (virB9 homologue) and is involved in the structural region of T4SS (type IV secretion system) [28]. The presence of these genes is associated with DU, DU, or GC with variable frequency between adult isolates from different geographic regions [16,19,22,23,26,29,30].…”
Section: Discussionmentioning
confidence: 99%